pH Variability Exacerbates Effects of Ocean Acidification on a Caribbean Crustose Coralline Alga - Johnson, Maggie D.; Rodriguez Bravo, Lucia M.; O’Connor, Shevonne E.; Varley, Nicholas F.; Altieri, Andrew H. (Frontiers in Marine Science, 2019)
Crustose coralline algae (CCA) are among the most sensitive marine taxa to the pH changes predicted with ocean acidification (OA). However, many CCA exist in habitats where diel cycles in pH can surpass near-future OA projections. The prevailing theory that natural variability increases the tolerance of calcifiers to OA has not been widely tested with tropical CCA. Here, we assess the response of the reef-building species Lithophyllum congestum to stable and variable pH treatments, including an ambient control (amb/stable). The amb/variable treatment simulated an ambient diel cycle in pH (7.65-7.95), OA/stable simulated constant low pH reflecting worst-case year 2100 predictions (7.7), and OA/variable combined diel cycling with lower mean pH (7.45-7.75). We monitored the effects of pH on total calcification rate and photophysiology (maximum quantum yield) over 16 weeks. To assess the potential for acclimatization, we also quantified calcification rates during the first (0-8 weeks) and second (8-16 weeks) halves of the experiment. Calcification rates were lower in all pH treatments relative to ambient controls and photophysiology was unaffected. At the end of the 16-week experiment, total calcification rates were similarly low in the amb/variable and OA/stable treatment (27-29%), whereas rates declined by double in the OA/variable treatment (60%). When comparing the first and second halves of the experiment, there was no acclimatization in stable treatments as calcification rates remained unchanged in both the amb/stable and OA/stable treatments. In contrast, calcification rates deteriorated between periods in the variable treatments: from a 16-47% reduction in the amb/variable treatment to a 49-79% reduction in the OA/variable treatment, relative to controls. Our findings provide compelling evidence that pH variability can heighten CCA sensitivity to reductions in pH. Moreover, the decline in calcification rate over time directly contrasts prevailing theory that variability inherently increases organismal tolerances to low pH, and suggests that mechanisms of tolerance may become limited with increasing time of exposure. The significant role of diel pH cycling in CCA responses to OA indicates that organisms in habitats with diel variability could respond more severely to rapid changes in ocean pH associated with OA than predicted by experiments conducted under static conditions.